Fox H-function: A study case on variate modeling of dual-hop relay over Weibull fading channels - De Lima, Carlos H. M. [UNESP]; Alves, Hirley; Nardelli, Pedro. H. J. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper proposes a novel analytical framework based on the Fox H-function distribution. To test its efficacy we focus on a study case where we derive closed form expressions for the distribution of the end-to-end signal to noise ratio, and corresponding outage probability for the dual-hop amplify-and-forward configuration over Weibull-fading channels with channel state information. An extensive simulation campaign was carried out to corroborate the proposed approach.
Keywords: Amplify-and-forward; H-function distribution; Machine-to-machine; Outage probability